Strategies and Counter-strategies for the Pharmaceutical and Fast-Food Industry - Koh, Malcolm Koh (SFU Health Sciences Undergraduate Journal, 2023)
Fast-food and pharmaceutical industries oversell the usefulness of their products and underplay the health consequences of overcomsumption through various corporate strategies. Unfortunately, there are many chronic disease epidemics that stem indirectly from corporate manipulation and deceit. For instance, older age demographics rely for pharmaceutical opioids for chronic pain relief management, and racialized demographics are unevenly exposed to marketing for fast foods.